Effect of Vitamin E, Vitamin C and Selenium on Blood Haematological, Biochemical, Liver Enzyme, Serum Electrolyte, Antioxidant Profile, Heat Shock Protein (HSP70) and Carcass Quality of Broiler Chickens During Heat Stress - Singh, Chandra Deep; Nath, Sudhanya; Gohain, A. K.; Tamuly, Shantanu; Bhuyan, Robin (Indian Journal of Animal Nutrition, 2023)
An experiment was conducted in 180-day-old vencobb 400 strain broilers chicks to determine the effects of Vitamin E, Vitamin C and Selenium in different combinations on blood haematological, biochemical, liver enzyme, serum electrolyte, heat shock protein, antioxidant profile and carcass quality of broiler chickens during heat stress. Chicks were distributed randomly into 5 groups having 36 chicks in each (3 replicates of 12 chicks). Control group (T0) was fed with basal ration and other four groups were offered basal ration and drinking water was supplemented with 100 mg/ltr vitamin E + 0.2 mg/ltr Se (T1), 100 mg/ltr vitamin E + 0.3 mg/ltr Se (T2), 100 mg/ltr vitamin E + 100 mg/ltr vitamin C (T3) and 200 mg/ltr vitamin E + 200 mg/ltr vitamin C (T4). Results showed significant difference (P